A Survey of Provenance in Wireless Sensor Networks - Dogan, Gulustan (OLD CITY PUBLISHING INC, 2016)
Provenance is a rapidly progressing new field with many open research problems. With the huge amount of information and processes available, provenance becomes crucial for understanding the creation, manipulation and quality of data and processes. Being related to data and processes, provenance research is at the cross road of research from several communities, such as databases, networks. However, there is a lot of confusion when comparing research efforts from different point of views. In this survey paper, we define provenance, provenance types, point out standardization approaches, describe provenance work in sensors network community to sketch a panoramic view of the recent research.
Keywords: Wireless sensor networks; provenance; open provenance model; workflow provenance; data provenance; trust; Computer Science; Telecommunications